Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea mays Saccharata) Terhadap Pemberian Pupuk Kandang Sapi dan Pupuk Organik Cair - Sitepu, Nico Armanda; Luta, Devi Andriani; Harahap, Ariani Syahfitri (UNIVERSITAS LABUHANBATU, 2025)
Efforts that can be made to increase corn productivity are by adding organic materials from plant residues and animal waste to the soil. This study aims to determine the effect of cow dung and liquid organic fertilizer from agricultural waste and their interactions on the growth and production of corn plants. This study used a Randomized Block Design with 2 factors and 3 replications to obtain 48 research plots. Factor I cow dung with the symbol